Shrimp by-catch reduction using a short funnel net, in the Gulf of Tehuantepec, South Pacific, Mexico - Saúl Sarmiento-Náfate (Revista de Biología Tropical, 2007)
Reduction of the by-catch in shrimp fishery is an important goal worldwide. In order to compare bycatch using the conventional trawling net and a newly designed short funnel net, nine cruises were carried out by the commercial fleet operating in the Gulf of Tehuantepec, Mexico. A total of 480 trawls were done (mean duration: 85 min). The experimental trawls using the modified net produced a 21.13-28.86 % by-catch reduction (confidence interval 95 %), a 3 % increase of shrimp catch, and a significant reduction on net recovery time.